RANKING FACTORS AFFECTING OF QUALITY OF SERVICES TO TELECOM CUSTOMERS IN ISFAHAN (Singaporean Journal of Business Economics and Management, 2015)
The main objective of this research was conducted to assess quality of the work method of customer service company in Isfahan was the gap analysis model using. The statistical community this research clients and visitors to the offices and the number of fixed telephone service centers of Isfahan were 1500000 which of these was estimated according to the Cochrane formula 384 people. Random sampling method in this study was stratified according to size. Questionnaire to assess the quality of information collected to assess validity of servqual questionnaire the questionnaire was cronbach's alpha coefficient (0.96) was used. The results showed that the levels of customer perception of service quality are not the same in all eight dimensions. Factors associated with the highest level of trust and Reliability Is at the lowest level. The following factors are also expected to have the highest level of trust and empathy is at lowest level.